"#DontCallMeABornFree": Lived experiences of a black umXhosa woman in post-apartheid South Africa. Issue 2 (3rd April 2018) - Maseti, Thandokazi
Abstract: The current realities of the so-called 'born free' generation call for a probing into how we define a 'born free'. The term 'born frees' is often used to refer to those who are enjoying the fruits of the liberation of South Africa, who are free from racial discrimination and benefitting from social transformation. However, the reality is that this generation faces greater poverty and racial and gender inequalities. I therefore argue that the term 'born free generation' is an ideology, and not necessarily one's reality. In the form of a personal story this profile piece uncovers my experiences while moving from different spaces in post-apartheid South Africa as a black 1 umXhosa woman. I highlight the socio-psychological impact of being a black umXhosa woman among different racial and ethnic groups. I also bring to the fore the deep scars that cut through to a generation regarded as 'born free', and later question whether we can really regard a generation that is born post-1990 as 'born free'.